SEMANTICS IN DIGITAL COMMUNICATION: AN ANALYSIS OF TEXT MESSAGE USAGE IN CLASS GROUPS BY GENERATION Z IN HIGHER EDUCATION - Kencana, Nila (La Ogi : English Language Journal, 2025)
This study investigates the use of digital communication in academic settings, specifically focusing on WhatsApp group chats among English Education students at Universitas Ahmad Dahlan (Unihaz), HIMABI 2024. The research analyzes the patterns of language use in chat messages, exploring the prevalence of informal language features such as abbreviations, emojis, and code-switching between Indonesian and English. The study also examines student perceptions regarding the impact of these language features on communication efficiency, clarity, and the overall academic atmosphere. The results reveal that informal language enhances engagement, fosters a supportive learning environment, and mitigates barriers to communication. However, the overuse of informal elements such as abbreviations and emojis can sometimes cause misunderstandings, particularly for students unfamiliar with these conventions. The study highlights the need for a balance between informality and academic rigor in digital communication. It concludes that while informal language serves an important role in student collaboration, educators should guide students in maintaining clarity and inclusivity in academic contexts